The Alienated Clara: intersectionality perspectives in Adrienne Kennedy’s The Owl Answers - Jabboury, Latifah Ismaeel; Ruzy Suliza Hashim; Anita Harris Satkunananthan (Penerbit Universiti Kebangsaan Malaysia, 2017)
Critical works on Adrienne Kennedy’s The Owl Answers have been limited to the domains of surrealism and to the frame of literary criticism which situate Clara, the protagonist of The Owl Answers within a psychological context. Many critics find that the play is a portrait of a black woman who is searching for home and belonging in a world of discrimination and inequality. Clara is often regarded as a mixed-raced woman of fragmented psyche who remains confused about her identity. Within the perspective of intersectionality, however, we contend that the study of Clara’s character acquires new dimensions of analysis. This article addresses Clara’s alienation within the scope of three intersectional categories of her identity: race, gender and hybridity. Clara tries her best to identify with her father’s white legacy, but all her efforts have been futile. As she recognizes that she has no hope at all to belong to this legacy, she feels entirely frustrated. The tragic outcome of The Owl Answers owes to psychological trauma experienced by Clara. We interrogate the overlapping oppressions endured by Clara through a study of how these three interlocking categories combine to shape her alienation right up to the point where it causes her to take her own life.